2005
DOI: 10.1111/j.1365-2982.2005.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic and clinical pharmacology of new motility promoting agents

Abstract: Recent research has provided new information about drugs that could be used to treat functional motility disorders. Promotility drugs accelerate gastric emptying or colonic transit and these properties may contribute to their efficacy in treating symptoms associated with gastroparesis, functional dyspepsia or constipation. 5-Hydroxytryptamine4 receptors are targets for drugs (tegaserod, renzapride) that treat symptoms in constipated irritable bowel syndrome patients and in gastroparesis. Drugs acting at motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 72 publications
(144 reference statements)
3
77
0
3
Order By: Relevance
“…Prokinetics, such as cisapride and mosapride, are a group of drugs that stimulate smooth muscle contraction to enhance GE and intestinal transit. 20,21) Recent studies have demonstrated that impaired gastric accommodation in FD may contribute to symptom generation. 22) Matsueda et al showed that acotiamide, a fundus-relaxing drug that acts via blockade of the M1/M2 muscarinic receptor, significantly improves the symptoms of FD and is more effective in reducing symptoms in patients with the postprandial distress syndrome of FD than in patients with epigastric pain syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Prokinetics, such as cisapride and mosapride, are a group of drugs that stimulate smooth muscle contraction to enhance GE and intestinal transit. 20,21) Recent studies have demonstrated that impaired gastric accommodation in FD may contribute to symptom generation. 22) Matsueda et al showed that acotiamide, a fundus-relaxing drug that acts via blockade of the M1/M2 muscarinic receptor, significantly improves the symptoms of FD and is more effective in reducing symptoms in patients with the postprandial distress syndrome of FD than in patients with epigastric pain syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Domperidone (Barone, 1999;Drolet et al, 2000) and tegaserod are both used therapeutically as prokinetic agents, although domperidone is often thought to be more effective on the proximal gut (Longo and Vernava, 1993;Jost, 1997) and so has been used to relieve the symptoms of dyspepsia and gastroparesis (Horowitz and Fraser, 1995;Tonini et al, 2004), whereas tegaserod is used to treat chronic constipation and constipation-predominant irritable bowel syndrome (Prather et al, 2000;Muller-Lissner et al, 2001;Johanson, 2004;Galligan and Vanner, 2005). Domperidone and DA, however, have both been shown to exert effects on the colon and rectum as well as on the upper bowel (Wiley and Owyang, 1987), whereas tegaserod accelerates gastric emptying (Degen et al, 2001;James et al, 2004;Crowell et al, 2005) and has also been useful in treating dyspepsia and gastroparesis (Banh et al, 2005;Galligan and Vanner, 2005;Zuberi et al, 2005). The acceleration by D 2 knock-out of total gastrointestinal and colonic motility suggests that D 2 receptors are important at all levels of the gut and are not restricted in their function to the proximal † † …”
Section: Discussionmentioning
confidence: 99%
“…Cholecystokinin, a neuropeptide secreted by endocrine cells of the duodenum, is released in response to the presence of lipids and/or fatty acids in the duodenal lumen. Circulating CCK inhibits gastric emptying (via vagal afferents) and gastric acid secretion (Cakir et al 2007;Shillabeer and Davison 1987) by activation of CCK1-type receptors in the stomach (localized to gastric smooth muscle cells and to peripheral terminals in the vagal afferent fibers) as well as in the central nervous system (Galligan and Vanner 2005).…”
Section: Delayed Gastric Emptyingmentioning
confidence: 99%